Towards a shared and supported decision-making model: fostering relational autonomy in end-of-life care - Foley, Geraldine; Hogan, Linda (My University, 2026)
Respecting patient autonomy is a fundamental ethical principle in end-of-life care (Farsides 1998). However, autonomy in this context cannot be reduced to an isolated act of self-governance, nor can its respect be confined to passive non-interference or the formal recording of consent. Faced with progressive illness, cognitive decline, emotional distress, and the existential weight of end-of-life decisions, many patients may struggle to articulate or sustain their preferences without appropriate forms of support (Elsner and Rampton 2022). To be meaningfully respected, autonomy must therefore be supported through relationships and institutional conditions that enable patients to reflect, deliberate, and make decisions aligned with their values and preferences (Bélanger et al. 2011). The question, then, is not solely how to respect patients’ autonomy in end-of-life care, but how autonomy, understood in relational terms, can be genuinely fostered. At the heart of this question lies a key philosophical debate: whether relational autonomy should be understood in procedural or in substantive terms (Mackenzie and Stoljar 2000), a distinction that fundamentally shapes what fostering autonomy means in practice, particularly in contexts marked by vulnerability and interdependence.
PUBLISHED